2020
DOI: 10.1002/cbic.202000585
|View full text |Cite
|
Sign up to set email alerts
|

Selective Affimers Recognise the BCL‐2 Family Proteins BCL‐xL and MCL‐1 through Noncanonical Structural Motifs**

Abstract: The BCL-2 family is a challenging group of proteins to target selectively due to sequence and structural homologies across the family. Selective ligands for the BCL-2 family regulators of apoptosis are useful as probes to understand cell biology and apoptotic signalling pathways, and as starting points for inhibitor design. We have used phage display to isolate Affimer reagents (non-antibody-binding proteins based on a conserved scaffold) to identify ligands for MCL-1, BCL-x L , BCL-2, BAK and BAX, then used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…To date, the majority of applications for Affimers have been as probes to support high-resolution imaging ( 51 , 52 ) or as antibody replacements in diagnostics and biosensor development ( 53 , 54 , 55 ). However, they have also proven to be powerful tools in the study of protein-protein interactions ( 56 , 57 ), with the capability to discriminate between very closely related proteins ( 58 ). Affimers have also been identified that are capable of modulating biological activities, either inhibiting viral replication ( 59 ) or SUMO-mediated protein interactions ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of applications for Affimers have been as probes to support high-resolution imaging ( 51 , 52 ) or as antibody replacements in diagnostics and biosensor development ( 53 , 54 , 55 ). However, they have also proven to be powerful tools in the study of protein-protein interactions ( 56 , 57 ), with the capability to discriminate between very closely related proteins ( 58 ). Affimers have also been identified that are capable of modulating biological activities, either inhibiting viral replication ( 59 ) or SUMO-mediated protein interactions ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins act through structural changes and drugs aim to block their action. A competitive drug binding mechanism is powerful since it directly blocks ligand docking 125,157–166 . A noncompetitive drug binding can be powerful by altering the active site shape, leading to the same outcome 167–177 .…”
Section: Molecular Activation Mechanism Matters In Drug Discoverymentioning
confidence: 99%
“…A competitive drug binding mechanism is powerful since it directly blocks ligand docking. 125,[157][158][159][160][161][162][163][164][165][166] A noncompetitive drug binding can be powerful by altering the active site shape, leading to the same outcome. [167][168][169][170][171][172][173][174][175][176][177] These drug actions typically target the active conformation.…”
Section: Molecular Activation Mechanism Matters In Drug Discoverymentioning
confidence: 99%
“…16 However, generally, sequence space is too great too explore using synthetic chemistry. Biological selection methods are powerful and do allow more space to be searched, [17][18][19] however, these can be experimentally demanding and expensive. For all these reasons, development and improvement of computational approaches to examine and design PPIs are important.…”
mentioning
confidence: 99%